Development of The Automotive Technology Vocational Education Curriculum Based on Current Needs of The Automotive Industry - Hardiyanta, Rendra Ananta Prima; Hermanto, Hermanto; Kurniawan, Arief; Purnawan, Purnawan; Prakoso, Ilham Eko (Jurnal Pendidikan Vokasi Otomotif, 2024)
This research aims to: 1) Analyze the competencies needed by the current automotive industry in the Automotive Industry, 2) Analyze the implications of the automotive industry's needs for the automotive technology vocational education curriculum, and 3) Analyze the supporting and inhibiting factors of the partnership program for the automotive technology vocational education study program. The subjects of this research were 5 practitioners consisting of: Service Manager, Instructor, Service Advisor, and Mechanic from the Business and Industrial World (DUDI) in the automotive sector in the Special Region of Yogyakarta. This research is a qualitative descriptive study. Data collection techniques in this research used observation, documentation and interview methods. The research instrument was validated through expert judgment. The data analysis technique uses qualitative descriptive analysis with the triangulation method to obtain data validity. The research results show that: 1) the competencies required by the current automotive industry for undergraduate graduates include technical competency and managerial competency; 2) The need for technical and managerial competency demands that curriculum study materials be adapted to industry needs; 3) Supporting factors for the partnership program include: complete industrial facilities and infrastructure and adequate human resources (HR). The inhibiting factors for the partnership program are: the absence of an MoU between agencies and difficulties in preparing schedules.